Prabu Siliwangi Dan Awal Islamisasi Di Tanah Sunda Antara Mitologi Dan Sejarah Politik - Basor, Saepul; Nurcahya, Yan; Sugiarto, Deri; Putra, Rian Ananda; Negara, Teddiansyah Nata; Hafidz, Muhammad Al; Hernawan, Wawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The process of Islamization in the Sundanese Lands is a complex historical phenomenon because it involves the interaction between political power, local culture, and traditional beliefs. The legendary figure of Prabu Siliwangi from the Pajajaran Kingdom is often positioned as a transitional figure between the Hindu-Buddhist era and the arrival of Islam in Tatar Sunda. In various oral sources, chronicles, and ancient manuscripts such as the Carita Parahyangan and Babad Pajajaran, Siliwangi is depicted as a great and just king, but also as a symbol of resistance to religious change. This figure is not only a mythological icon, but also a reflection of the struggle of Sundanese cultural identity facing the increasingly strong current of Islamization in the 15th to 16th centuries AD. This study aims to explore the relationship between the mythology of Prabu Siliwangi and the early process of Islamization in the Sundanese Lands through a historical and politico-cultural approach. Using descriptive-analytical methods and a literature review of historical sources, legends, and archaeological research results, this study attempts to interpret Siliwangi's position in the context of civilizational transition. The analysis shows that the Siliwangi myth functions as an ideological medium to maintain political legitimacy and local identity amidst religious change. Thus, the narrative about Siliwangi not only contains elements of legend, but also reflects the socio-political and spiritual dynamics of Sundanese society during the transition to Islam.